Identification and chemical profiling of anti-alcoholic liver disease biomarkers of ginseng Huang jiu using UPLC-Q-Orbitrap-HRMS and network pharmacology-based analyses - Wu, Yongxi; Cai, Yongyu; Ma, Liting; Li, Fangtong; Zhang, Meiyu; Wang, Yizhu; Zheng, Fei; Pi, Zifeng; Yue, Hao (Frontiers in Nutrition, 2022)
This study investigated the mechanism of characteristic non-volatile organic compounds (NVOCs) from ginseng Huang jiu (GH) in the treatment of alcoholic liver disease through UPLC-Q-Orbitrap-HRMS and network pharmacological analyses. Changes in NVOC contents in ginseng Huang jiu and ginseng-soaked wine fermented by different processing technologies were analyzed through liquid chromatography–mass spectrometry (LC-MS). A total of 96 ginsenosides were identified in ginseng Huang jiu throughout the fermentation process, which included 37 protopanaxadiol-type ginsenosides, 47 protopanaxatriol-type ginsenosides, and 4 oleanolic acid-type ginsenosides. Orthogonal partial least squares-discriminant analysis (OPLS-DA) revealed that 20(R)-Rg2, Gypenoside XVII, 20(S)-Rf3, CK, Rg5, Rh2, and other rare ginsenosides in ginseng Huang jiu could be the potential index for determining ginseng Huang jiu. In addition, ginseng Huang jiu could improve alcoholic liver disease by regulating the GSTP1, HRAS, AKR1B1, GSTA1, Androgen receptor (AR), GSR, and LDHB genes through bioinformatics analysis. This study provides new insights into improving the industrial production of ginseng Huang jiu and treating alcoholic liver disease with medicinal and food products.